IL-11/IL11RA receptor mediated signaling: a web accessible knowledgebase. (August 2013) - Balakrishnan, Lavanya; Soman, Sowmya; Patil, Yatish B.; Advani, Jayshree; Thomas, Joji Kurian; Desai, Dattatraya Venkatesh; Kulkarni-Kale, Urmila; Harsha, H. C.; Prasad, T. S. Keshava; Raju, Rajesh; Pandey, Akhilesh; Dimitriadis, Eva; et al.
Abstract: Interleukin-11 (IL-11) is a pleiotropic cytokine that belongs to gp130 family. It plays a significant role in the synthesis and maturation of hematopoietic cells, inhibition of adipogenesis, regulation of embryo implantation, and trophoblasts invasion. Although IL-11 signaling has been described in several biological processes, a centralized resource documenting these molecular reactions induced by IL-11 is not publicly available. In the current study, we have manually annotated the molecular reactions and interactions induced by IL-11 from literature available. We have documented 40 unique molecules involved in 18 protein–protein interactions, 26 enzyme–substrate reactions, 7 translocation events, and 4 activation/ inhibition reactions. We have also annotated 23 genes reported to be differentially regulated under IL-11 stimulation. We have enabled the data availability in standard exchange formats from 'NetPath', a repository for signaling pathways. We believe that this will help in the identification of potential therapeutic targets in IL-11-associated disorders.